Biomarkers and Community-Acquired Pneumonia: Tailoring Management with Biological Data - Torres, Antoni; Ramirez, Paula; Montull, Beatriz; Menéndez, Rosario (Seminars in Respiratory and Critical Care Medicine, 2012)
Community-acquired pneumonia (CAP) is the leading cause of death from infectious diseases worldwide, with an incidence of 0.3 to 0.5% in the adult population. A new diagnostic and prognostic approach relies on evaluation of biomarkers as an expression of the host's inflammatory response against the microorganism. C-reactive protein (CRP), procalcitonin (PCT), and cytokines are the most frequently studied, whereas pro-adrenomedullin (pro-ADM), pro-vasopressin (pro-VNP), and others are currently obtaining promising results. Their usefulness for diagnosis is limited, although PCT has been successfully used to guide prescription of antibiotics in patients with suspected CAP. Nevertheless, the accuracy of PCT in distinguishing between bacterial or viral infection and safely withholding antibiotics in CAP is the subject of debate. Analysis of systemic biomarkers in addition to clinical scores [Pneumonia Severity Index (PSI) or CURB-65 (confusion, urea, respiratory, blood pressure, >65 years)/CRB-65 (confusion, respiratory, blood pressure)] has been shown to improve 30 day mortality prediction and absence of severe complications. Pro-ADM is probably the biomarker that correlates most strongly with mortality prediction. During treatment, ~15% of hospitalized CAP patients develop treatment failure, and almost 6% may manifest rapidly progressive pneumonia. Initially increased and persistent raised levels of biomarkers and cytokines have been shown to identify patients at risk of treatment failure, thereby aiding clinical management. Data from the literature appear to support the use of biomarkers in routine clinical practice to improve the decision making in CAP.
Keywords: cytokine; diagnosis; treatment